Differences between pension systems of the EU states - Krejčí, Jan (2016)
This thesis focuses on the issue of European pension systems from a standpoint of their structure and sustainability in view of ageing of the population. The structure of systems is examined through pension models which embody combinations of financing (pay-as-you-go or capital funded) and pension calculation (defined contribution or defined benefit). The main object is to reveal how much are the European pension systems threatened by ageing of the population and sort them out according to this discovery. The risk rate is calculated as a ratio of the difference between expense rate on public pension pillars in 2012 and 2060 to the difference between dependency ratio in the same interval. The final figure shows the percentage of relative expenses per capita in 2060 compared to the base year of 2012. The main object is carried out by dividing the studied states into three groups. According to thesis' results, the most endangered state is Poland with a value of 28 % while the least endangered state is Luxembourg with a value of 110 % or relative expenses per capita compared to the base year of 2012.